Housing Condition and Basic Infrastructural Facilities of Handloom Weavers – A Case Study - Shazli, Tasneem; Munir, Abdul (National Geographical Journal of India, 2022)
Housing which is one of the basic human needs after food and clothing, provides adequate shelter and significant socio-economic security. Along with the requirement of shelter, basic infrastructure facilities contribute a vital role in the development of quality of life. During the time of Moguls skilled Muslim weavers came to India and settled in Varanasi and nearby areas. Therefore weaving became the major occupation of Mubarakpur Town. It is gradually declining from last few decades due to economic and political reasons. The decline of handloom sector has adversely affected the socio-economic conditions of weavers. The objective of this paper is to assess the housing condition and infrastructural facilities of handloom weavers of Mubarakpur town in 2015. The study is based on primary data collected through a detailed questionnaire. Results show that housing condition and infrastructural facilities is not satisfactory in the town. The deteriorating situation is visible by going through the housing condition of the handloom weavers. The study further suggests some remedial measures for the development of housing status and infrastructure facilities of handloom weavers.